2023
DOI: 10.3847/2041-8213/acbc73
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Length of the Heliospheric Tail with Energetic Neutral Atoms (ENAs) from 0.52 to 80 keV

Abstract: The shape of the heliosphere is currently under active debate. Energetic neutral atoms (ENAs) offer the best method for investigating the global structure of the heliosphere. To date, the Interstellar Boundary Explorer (IBEX) and the Ion and Neutral Camera (INCA) that was on board Cassini provide the only global ENA observations of the heliosphere. While extensive modeling has been done at IBEX-Hi energies (0.52–6 keV), no global ENA modeling has been conducted for INCA energies (5.2–55 keV). Here, we use an E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…The energy partition was used to obtain the PUI properties from the plasma mixture instead of solving the equations describing the PUI behavior self-consistently. Recently, Kornbleuth et al (2023) have used the hybrid simulations of Giacalone et al (2021) and the theoretical analysis of Wang et al (2023) to investigate the effect of diffusive shock acceleration on the PUI transmission through the TS in the framework of a global model, which did not include PUIs separately. In addition, rather strong assumptions were made to extrapolate or deduce the properties of PUIs across the entire TS surface and the IHS, with the purpose of fitting the IBEX and Cassini INCA measurements of ENA fluxes in the energy range up to 40 keV.…”
Section: Treatment Of Puis Across the Termination Shockmentioning
confidence: 99%
“…The energy partition was used to obtain the PUI properties from the plasma mixture instead of solving the equations describing the PUI behavior self-consistently. Recently, Kornbleuth et al (2023) have used the hybrid simulations of Giacalone et al (2021) and the theoretical analysis of Wang et al (2023) to investigate the effect of diffusive shock acceleration on the PUI transmission through the TS in the framework of a global model, which did not include PUIs separately. In addition, rather strong assumptions were made to extrapolate or deduce the properties of PUIs across the entire TS surface and the IHS, with the purpose of fitting the IBEX and Cassini INCA measurements of ENA fluxes in the energy range up to 40 keV.…”
Section: Treatment Of Puis Across the Termination Shockmentioning
confidence: 99%
“…The neutral particles are described kinetically using a Monte Carlo method. While two different ENA models are used in the different MHD models, Kornbleuth et al (2021bKornbleuth et al ( , 2023b showed that using the same ENA model in both MHD solutions produced quantitatively similar ENA maps.…”
Section: Modelsmentioning
confidence: 99%
“…PUIs created in the heliosheath had been previously ignored in the modeling of Kornbleuth et al (2023b) due to their contributions at lower energies. Here, the IHS PUIs are included as well.…”
Section: The Boston Modelmentioning
confidence: 99%
See 2 more Smart Citations